2019
DOI: 10.1029/2019gl082731
|View full text |Cite
|
Sign up to set email alerts
|

High Contribution of Secondary Brown Carbon to Aerosol Light Absorption in the Southeastern Margin of Tibetan Plateau

Abstract: The optical properties of atmospheric secondary brown carbon (BrC) aerosol are poorly understood because of its chemical complexity, and this has hampered quantitative assessments of the impacts of this light‐absorbing material on glaciers on the Tibetan Plateau. For this study, a statistical approach was developed to investigate BrC light absorption over the southeastern margin of the Tibetan Plateau. Secondary sources for BrC were more important for absorption than primary ones. A diurnal cycle in secondary … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
81
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 99 publications
(88 citation statements)
references
References 83 publications
7
81
0
Order By: Relevance
“…S4). A slope of 2.3 was regarded as the correction factor and was comparable to the values of 2.0-2.6 reported by previous studies using a similar method (Qin et al, 2018;Tasoglou et al, 2017;Wang et al, 2019b). This difference may mainly be related to the matrix scattering and lensing effects.…”
Section: Overview Of Abs(λ)supporting
confidence: 77%
See 1 more Smart Citation
“…S4). A slope of 2.3 was regarded as the correction factor and was comparable to the values of 2.0-2.6 reported by previous studies using a similar method (Qin et al, 2018;Tasoglou et al, 2017;Wang et al, 2019b). This difference may mainly be related to the matrix scattering and lensing effects.…”
Section: Overview Of Abs(λ)supporting
confidence: 77%
“…Additionally, the MAC BrC,biomass (λ) was several times to 2 orders of magnitude lower than MAC BC (λ) from different sources, suggesting that BC had a stronger ability to absorb light compared to BrC. Notably, the MAC BrC (λ) obtained in this study was within the range reported by previous investigations, although with differences among studies (Wang et al, 2019b;Cho et al, 2019). The differences in MAC BrC (λ) may partly be related to biomass types and their burning efficiencies as well as the aging processes of BrC in the atmosphere.…”
Section: Source-dependent Optical Properties Of Lac Aerosolssupporting
confidence: 71%
“…for each day, which were computed using the NOAA HYSPLIT4 model, and the clusters analysis results, as shown in Figure S1b, showed that during the sampling periods, air masses transported mainly from the west and southwest (mainly in the northeast part of Burma and the Sino-Burmese border) to Gaomeigu accounted for 65.6% and 39.7% of all of the trajectories, respectively, and only 5% of the air masses transported from the east (inner China). This indicates the important influence of Southeast Asia, where intensive burning activities or natural forest fires occur frequently during the premonsoon season [16,49]. In addition, there were two significant build-ups for different atmospheric pollutant periods-from 22 to 26 March (Period 1: five days, with a PM 2.5 average of 34.67 µg m −3 ) and 25 to 27 April (Period 2: three days, with a PM 2.5 average of 40.61 µg m −3 ).…”
Section: Concentration-weighted Trajectory (Cwt) Analysismentioning
confidence: 99%
“…A BC-tracer method was utilized to separate Abssec(λ) from Abspri(λ) (Wang et al, 2019a). Thus, the Eq.…”
Section: Segregation Of Bc and Brc Absorptionmentioning
confidence: 99%
“…1%' ratio was determined with a minimum R-squared (MRS) method, which is described in detail in Wang et al (2019a).…”
Section: Segregation Of Bc and Brc Absorptionmentioning
confidence: 99%